ROLE OF SHYAMA TRIVIT (OPERCULINA TURPETHUM) AND SATAMULI (ASPARAGUS RACEMOSUS) IN THE MANAGEMENT OF PARINAMSHOOLA (PEPTIC ULCER) (AYUSHDHARA, 2020)
In action-pathological consideration of Parinam shoola state Acharya Madhav has described that Vayu is dearranged on account of its Specific aetiological factors followed by the involvement of Pitta and Kapha, becomes more powerful and Produces Shoola (Pain). In general it is seen in Vatapitta Purusha. In clinical study 40 patients have been selected for clinical trial. Though different data have been showed in the different groups yet it has been established in my study as like modern peptic ulcer disease as a ulcer healing and gastric anti-secretory agent have also used in Ayurvedic drug like Shyamatrivit and Satamuli as a gastric anti-secretory and ulcer healing drug. Patients in respective of their age sex, religion, habitat, occupation, educational status, income status, Prakriti etc. These 40 patients were randomly categorized in four groups (i.e. A.B.C.D) in respective their age, sex, etc. Ten (10) number of patients in group ‘A’ was treated with Shyamatrivit churna 2gm twice daily before meal for 8 weeks. Twelve patients of Group B were treated with Satamuli Churna 3gm twice daily before meal with water for 8 weeks Ten patients of Group-C were treated with Shyamatrivit 2gm and Satamuli 3gm before principle meal with water for 8 weeks. Fine powder of rice 1gm twice daily after meal for 8 weeks treated Group-D (Placebo Group) total number of 8 patients. After treatment of Group– A 2 patients get complete relieves about 10 patients. Group B: 4 patient, Group – C: 7 patient Group – D: get complete relieves about 1 patient. It symptomatic relief it has been observed that Group A, B, C patients showed significant improvement of receiving sing and symptoms while comparing before and 8 weeks after treatment of same group of patients. Among these three group the group – C i.e., Shyamatrivit and Satamuli jointly): exerted better effect than single use of Shyamatrivit and Satamuli also shows good results than Shyamatrivit.